Melanesian farmers conserve banana diversity - Fanton, Michel (Technical Centre for Agricultural and Rural Cooperation, 2005)
A local NGO on the island of Makira in the southeastern Solomon Islands is helping subsistence farmers to conserve their hundreds of banana varieties...